2021
DOI: 10.1038/s41598-021-03834-3
|View full text |Cite
|
Sign up to set email alerts
|

A Klebsiella pneumoniae DedA family membrane protein is required for colistin resistance and for virulence in wax moth larvae

Abstract: Ineffectiveness of carbapenems against multidrug resistant pathogens led to the increased use of colistin (polymyxin E) as a last resort antibiotic. A gene belonging to the DedA family encoding conserved membrane proteins was previously identified by screening a transposon library of K. pneumoniae ST258 for sensitivity to colistin. We have renamed this gene dkcA (dedA of Klebsiella required for colistin resistance). DedA family proteins are likely membrane transporters required for viability of Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…These results seem different from those observed in K. pneumoniae by Cheng et al who demonstrated that CrrC, an ortholog gene of ECL_01760, regulated the pmrHFIJKLM operon, also called arnBCADTEF , and pmrC through the PmrAB TCS ( 25 ). Interestingly, in K. pneumoniae , the small protein DkcA, displays similarity to membrane transporter and is required for CST resistance in a lipid A-dependent and-independent manner ( 39 ). DkcA is required for lipid A modification with Ara4N by a yet unidentified mechanism, but authors hypothesized that it would play a role in the arn pathway or by maintaining an inner membrane potential necessary for the CST antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…These results seem different from those observed in K. pneumoniae by Cheng et al who demonstrated that CrrC, an ortholog gene of ECL_01760, regulated the pmrHFIJKLM operon, also called arnBCADTEF , and pmrC through the PmrAB TCS ( 25 ). Interestingly, in K. pneumoniae , the small protein DkcA, displays similarity to membrane transporter and is required for CST resistance in a lipid A-dependent and-independent manner ( 39 ). DkcA is required for lipid A modification with Ara4N by a yet unidentified mechanism, but authors hypothesized that it would play a role in the arn pathway or by maintaining an inner membrane potential necessary for the CST antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…The DedA family proteins are highly conserved membrane proteins, but they are poorly characterized and their functions still remain unknown. However, there are some hypotheses that the DedA family proteins can function as the proton-dependent transporters, provide colistin resistance and take part in the normal cell division [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…It is found in all major bacterial clades except for the peptidoglycan-less Tenericutes and the Thermotogota (Table 1). Almost all experimentally studied bacterial DedAs are in this family, including the sole (and essential) DedA of Borrelia burgdoferi (11), the target of the antibiotic halicyclamine A in Mycobacterium smegmatis (12), as well as DedAs implicated in colistin resistance through 4-amino-4-deoxy-Larabinose modification of Lipid A in Klebsiella pneumoniae (13), Enterobacter cloacae (14), Burkholderia thailandensis (15), and Burkholderia glumae (16), and others (17)(18)(19).…”
Section: Cog0586 Deda Proteins Are Putative Undp Flippasesmentioning
confidence: 99%